Participatory approach to improve dietary diversity in Vihiga County, Western Kenya [Abstract] - Boedecker, J.; Oduor F.; Termote, Céline; Kennedy G. (Bioversity International, 2017)
Abstract accepted for poster presentation at 3rd International Congress Hidden Hunger: Post-2015 Agenda and Sustainable Developmental Goals (SDG): Where are we now? Strategies to improve nutrition quality and combat hidden hunger, Stuttgart, Germany, March 20-22, 2017